J03 Comparing IMU outputs between 1st team and U18 female soccer players throughout preseason - Smith, Anna; Donnelly, Julia; White, Andrew; Scobie, Nairn (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
With growth in professionalism, popularity and revenue in women’s soccer, greater investment is being made throughout academy environments to ensure young players can reach the physical, physiological, and technical demands of the sport. However, limited evidence exists to support the transition at club level between youth academy and senior players, and there is ambiguity in determining differences in physical loading. Thus, this study aimed to compare physical inertial measurement units (IMU) outputs between female U18 academy players and professional soccer players throughout pre-season. Participants were recruited from the same Scottish women’s soccer team U18 squad (n = 19, mean ± SD age = 16.5 ± 0.6 years) and 1st Team (n= 23, mean ± SD age = 25.1 ± 5.6 years) during the 2023/24 season. Top speed (m/s), distance covered (m), sprint count (n), and count of acceleration and deceleration actions (n) from IMU output were analysed (Playermaker). Descriptive statistics summarised key findings, with inferential methods utilised to determine variances between squads. Multivariate tests reported statistical significance at P < 0.05 between squads for physical metrics measured from 66 training sessions and 10 games. Results found mean weekly distance was significantly higher for U18 players in comparison to 1st team (6,252 ± 1,480 vs. 5,076 ± 2,064 m, P < 0.01). Mean weekly top speed was significantly higher in 1st team in comparison to U18 squad (6.33 ± 0.34 vs. 6.03 ± 0.34 m·s−1, P < 0.01). Mean weekly sprint count was significantly higher in 1st team versus U18 (11 ± 10 vs. 5 ± 5, P < 0.01). No significant differences were highlighted for count of acceleration and deceleration actions between squads (P > 0.05). These findings show that although U18s are exposed to a greater volume, this is performed at lower intensities within the pre-season window, and therefore potentially not replicating the high intensity intermittent nature of the game. These findings suggest the introduction of individualised speed thresholds appropriate for developmental state. Furthermore, formatting future training to incorporate more anaerobic physiological adaptations to help prepare academy players for the physical demands of professional soccer.